2017
DOI: 10.1007/s10552-017-0912-0
|View full text |Cite
|
Sign up to set email alerts
|

Urgent need to strengthen and expand screening and other cancer control programs in the CARICOM Caribbean

Abstract: There is an urgent need to develop and implement comprehensive and customized cancer control policies addressing screening programs, treatment and palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A recent review of Caribbean cancer screening programs revealed that for 12 countries that have BC screening services available, mammography is not available in the public sector for more than half of them. 107 It is then plausible that Caribbean women with private insurance and those with higher socioeconomic status may have better access to mammography. Furthermore, although traveling abroad to other countries for BC screening is unlikely, for those who can afford it, traveling abroad to other Caribbean countries (eg, Trinidad, Martinique, or Puerto Rico), the United States, the United Kingdom, or France for confirmation of a BC diagnosis or for treatment may be an option.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of Caribbean cancer screening programs revealed that for 12 countries that have BC screening services available, mammography is not available in the public sector for more than half of them. 107 It is then plausible that Caribbean women with private insurance and those with higher socioeconomic status may have better access to mammography. Furthermore, although traveling abroad to other countries for BC screening is unlikely, for those who can afford it, traveling abroad to other Caribbean countries (eg, Trinidad, Martinique, or Puerto Rico), the United States, the United Kingdom, or France for confirmation of a BC diagnosis or for treatment may be an option.…”
Section: Discussionmentioning
confidence: 99%
“…Although BC screening is widely available in the CARICOM Caribbean, services are not part of structured or comprehensive screening programs or follow defined national policies, as recommended by the WHO [ 6 ]. Spence et al [ 9 ] reported that only seven CARICOM countries (Belize, Jamaica, Guadeloupe, Martinique, Puerto Rico, Suriname, and Trinidad and Tobago) have operational, stand-alone national cancer control plans.…”
Section: Reviewmentioning
confidence: 99%
“…This is also seen in South America, which lies within the same geographical region as the Caribbean, which has similar incidence rates, yet the Caribbean suffers higher mortality comparable to that of Africa. As the Caribbean Community (CARICOM) has approximately 83% Afro-Caribbean people (6% East Indian, 9% mixed, and 2% others) [ 6 ], investigations into genetic and ethnic predisposition of BC need to be studied. Additionally, further epidemiological investigations into the factors associated with BC outcomes observed in the Caribbean population are imperative for improving survivorship.…”
Section: Introductionmentioning
confidence: 99%